Detection of Mycoplasma gallisepticum and Mycoplasma synoviae in Fertile Eggs by ELISA and Real-Time PCR - J Ali, Abtisam; Nijres, Al.T.; A Faraj, Rawah (The Iraqi Journal of Veterinary Medicine, 2024)
This study aimed to assess the occurrence of Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS) infections in fertile eggs using Enzyme-linked Immunosorbent Assay (ELISA) and Real-Time PCR. A total of 62 yolk samples were collected from August 2022 to April 2023. Of these, 31 samples (50%) were tested positive for antibodies via ELISA, while 13 samples (21%) were positive using Real-Time PCR. Specifically, 10 samples (16.12%) were positive for MG, and 3 samples (4.83%) were positive for MS, indicating a higher incidence of MG than MS in the hatcheries examined. The results suggest that maternal antibodies detected by ELISA may confer protection to chicks against MG and MS. This study confirms the vertical transmission of MG and MS from hens to their fertile eggs. The findings underscore the need for enhanced quality control measures and better management practices in hatcheries to mitigate the risk of Mycoplasma infections and improve overall poultry health